2008
DOI: 10.1007/bf03346383
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers for cardiovascular risk following treatment in endogenous Cushing’s syndrome

Abstract: Our findings suggest a complex interaction between CS and inflammation. In particular, the raised levels of IL-8 and OPG in CS patients, despite glucocorticoid excess, may represent an inflammatory and pro-atherogenic phenotype. However, the clinical relevance of these findings will have to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…These parameters all improved or normalized after successful therapy (180,181,182,183). specifically with the length of exposure to GCs, and functional modifications have been also reported.…”
Section: European Journal Of Endocrinologymentioning
confidence: 75%
“…These parameters all improved or normalized after successful therapy (180,181,182,183). specifically with the length of exposure to GCs, and functional modifications have been also reported.…”
Section: European Journal Of Endocrinologymentioning
confidence: 75%
“…According to our results, Kristo et al in a longer follow-up period (range 5-69 months) observed the persistence of high OPG values after CS remission. The authors correlated the absence of OPG normalization with an increased inflammation pattern persistence, which might represent a pro-atherogenic profile (32).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, during a 3-month period of high-dose GC treatment (60 mg prednisolone per day), it was observed that OPG decreased after 2 weeks and returned to baseline after 3 months, while soluble RANKL serum levels increased (30). In contrast, considering CS, in three studies, OPG serum levels were found to be higher in patients compared to healthy controls (14,31,32). The increased OPG levels in CS might be a compensation to protect bone from the damage that occurs in long and uncontrolled endogenous cortisol excess, while the decrease in OPG in GC-treated patients could reflect the direct effect of GC on osteoblastic cells.…”
Section: Discussionmentioning
confidence: 97%
“…Plausibly, steroids, especially corticosteroids, are associated with attenuated degrees of VEGF-induced angiogenic responses in humans (13) and in experimental animal models (16,25). Serum VEGF levels are elevated in patients with Cushing's syndrome when compared with those suffer from essential hypertension (18), suggesting some functional linkages of VEGF and steroid pathways in humans. We propose that regulation of caveolin-1 abundance by nuclear steroid receptor pathways may uncover a novel mechanism at which exposure to excess steroids, including agonists for GR and MR, leads to perturbed sensitivities of vascular endothelium to angiogenic growth factors such as VEGF.…”
Section: Discussionmentioning
confidence: 99%